Fc gamma receptor IIIb enhances Fc gamma receptor IIa function in an oxidant-dependent and allele-sensitive manner. - Salmon, J E (1995)
Two classes of receptors for IgG, Fc gamma RIIa and Fc gamma RIIIb, both of which exist in two allelic forms, are expressed on human neutrophils. Neutrophils from normal donors, homozygous for the different allelic phenotypes of Fc gamma RIIIb, have significantly different levels of Fc gamma receptor-mediated phagocytosis of IgG-opsonized erythrocytes (EA). However, the observation that Fc gamma RIIIb mediates phagocytosis of specific mAb-targeted erythrocytes poorly suggests that this receptor may influence EA internalization by Fc gamma RIIa in an allele-sensitive fashion. Donors homozygous for the NA1 allele of Fc gamma RIIIb showed greater activation of Fc gamma RIIa after Fc gamma RIIIb cross-linking than donors homozygous for the NA2 allele of Fc gamma RIIIb. This increase in receptor-specific internalization reflects both an increase in ligand binding by Fc gamma RIIa and an increase in internalization efficiency of targets bound. Activation of Fc gamma RIIa by Fc gamma RIIIb is transferable by supernatants from activated cells and is blocked by inhibitors of reactive oxygen species and the H2O2-myeloperoxidase-chloride system and by serine protease inhibitors. Thus, cross-linking of Fc gamma RIIIb, which leads to neutrophil degranulation and the generation of reactive oxygen intermediates, in turn alters Fc gamma RIIa avidity and efficiency. These oxidant-mediated changes in Fc gamma RIIa function provide a novel mechanism for receptors to collaborate in both an autocrine and paracrine fashion. The allele sensitivity of these effects suggests that Fc gamma receptor polymorphisms may be inherited disease susceptibility factors in host defense against infection and in the development of autoimmunity.